The Girl Who Played with Fire - Book 2 - Larsson, Stieg 1954-2004.; Keeland, Reg 1943- (New York : Vintage Book / Black Lizzard, 2009)
Two reporters responsible for a sex-trafficking exposé are murdered, and the fingerprints on the murder weapon belong to Lisbeth Salander, prompting the magazine's publisher, Mikael Blomkvist, to launch his own investigation to vindicate Salander.
Keywords: Fiction